Culturally proficient leadership :The Personal Journey begins within - Terrell, Eloise K.; Terrel,Raymond D; Lindsey, Randall B.; Lindsey, Delores B.; Alpert, Dan (Corwin, 2018)
Becoming a culturally proficient leader requires the kind of courage, clarity, and insight that can only come from looking inward first. It's a personal learning journey of will and skill, and if you're up to the challenge, one that will change how you see your school, your students, and yourself as you build your own cultural competence. Consider this second edition of Culturally Proficient Leadership your personal road map for navigating that journey. Each chapter of Culturally Proficient Leadership invites you to put your experiences up front and challenges you to reframe your story based on multiple viewpoints--now, notably, with the addition of new coauthors Delores Lindsey and Eloise Kemp Terrell, who have their own remarkable stories and insight to share -- Provided by the publisher.